High Efficiency Perovskite‐Silicon Tandem Solar Cells: Effect of Surface Coating versus Bulk Incorporation of 2D Perovskite. Issue 9 (31st January 2020) - Duong, The; Pham, Huyen; Kho, Teng Choon; Phang, Pheng; Fong, Kean Chern; Yan, Di; Yin, Yanting; Peng, Jun; Mahmud, Md Arafat; Gharibzadeh, Saba; Nejand, Bahram Abdollahi; Hossain, Ihteaz M.; et al.
Abstract: Mixed‐dimensional perovskite solar cells combining 3D and 2D perovskites have recently attracted wide interest owing to improved device efficiency and stability. Yet, it remains unclear which method of combining 3D and 2D perovskites works best to obtain a mixed‐dimensional system with the advantages of both types. To address this, different strategies of combining 2D perovskites with a 3D perovskite are investigated, namely surface coating and bulk incorporation. It is found that through surface coating with different aliphatic alkylammonium bulky cations, a Ruddlesden–Popper "quasi‐2D" perovskite phase is formed on the surface of the 3D perovskite that passivates the surface defects and significantly improves the device performance. In contrast, incorporating those bulky cations into the bulk induces the formation of the pure 2D perovskite phase throughout the bulk of the 3D perovskite, which negatively affects the crystallinity and electronic structure of the 3D perovskite framework and reduces the device performance. Using the surface‐coating strategy with n ‐butylammonium bromide to fabricate semitransparent perovskite cells and combining with silicon cells in four‐terminal tandem configuration, 27.7% tandem efficiency with interdigitated back contact silicon bottom cells (size‐unmatched) and 26.2% with passivated emitter with rear locally diffused silicon bottom cells is achieved in a 1 cm 2 size‐matched tandem. Abstract : Surface coating of 3D perovskite with alkylammonium bulky cations passivates the surface defects and improves the perovskite solar cell performance, while incorporating those cations into the bulk negatively affects the crystallinity and reduces the device performance. Using the surface‐coating strategy, four‐terminal perovskite‐silicon tandem reaches an efficiency of 27.7% with interdigitated back contact silicon bottom cells.